2020
DOI: 10.1093/infdis/jiaa159
|View full text |Cite
|
Sign up to set email alerts
|

A High-Fat Diet Increases Influenza A Virus-Associated Cardiovascular Damage

Abstract: Background Influenza A virus (IAV) causes a wide range of extrarespiratory complications. However, the role of host factors in these complications of influenza virus infection remains to be defined. Methods Here, we sought to use transcriptional profiling, virology, histology, and echocardiograms to investigate the role of a high-fat diet in IAV-associated cardiac damage. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…In mice, diets rich in lipids/fat seem to play a crucial role in both respiratory and extra-respiratory complications of influenza A virus infection, related to an increase in viral load in the lungs and heart. This deficient antiviral response has been associated with signaling defects in the inflammatory response in mice, leading to high lung inflammation and damage, as well as increased heart inflammation and damage, i.e., increased left ventricular thickness and mass [ 82 ]. A high-fat diet administration in mice has also been associated with an efficacy reduction in influenza vaccine through a reduced antibody response, due to macrophage dysfunction in fatty environments [ 83 , 147 ].…”
Section: Dietary Constituents As Key Factors Of a Strong Immune Symentioning
confidence: 99%
“…In mice, diets rich in lipids/fat seem to play a crucial role in both respiratory and extra-respiratory complications of influenza A virus infection, related to an increase in viral load in the lungs and heart. This deficient antiviral response has been associated with signaling defects in the inflammatory response in mice, leading to high lung inflammation and damage, as well as increased heart inflammation and damage, i.e., increased left ventricular thickness and mass [ 82 ]. A high-fat diet administration in mice has also been associated with an efficacy reduction in influenza vaccine through a reduced antibody response, due to macrophage dysfunction in fatty environments [ 83 , 147 ].…”
Section: Dietary Constituents As Key Factors Of a Strong Immune Symentioning
confidence: 99%
“…SARS-CoV-2 titres in cell culture supernatants were determined by plaque assay on Vero cells, as described previously (28). Influenza virus titers in cell culture supernatants were determined by plaque assay on MDCK cells, as described previously (29).…”
Section: Quantification Of Infectious Virusmentioning
confidence: 99%
“…[7] In addition, the use of High-Fat Diet (HFD) in rats increased macrophage infiltration to lung tissues, specifically in the alveoli. [8] Recently, Siegers et al [9] demonstrated that HFD increases influenza A virus-associated cardiovascular damage in mice. This is particularly pertinent to COVID-19 patients agreed on the high rate of infection among lung alveolar epithelial cells and the taking part of lung tissue inflammation and alveolar damage in COVID-19 morbidity.…”
Section: Dietary Habits: Fast Foodsmentioning
confidence: 99%